2002
DOI: 10.1039/b201575g
|View full text |Cite
|
Sign up to set email alerts
|

Forensic glass analysis by ICP-MS: a multi-element assessment of discriminating power via analysis of variance and pairwise comparisons

Abstract: Ti) to use for discrimination among the glass samples. This multi-element discrimination showed a significant improvement in the discrimination statistics over using only refractive index (RI) measurements. Oak Ridge National Laboratory (ORNL) recently analyzed fragments from 76 of the original side window fragments using inductively coupled plasma mass spectrometry (ICP-MS). The ICP-MS analyses measured 45 elements using a hierarchical sampling scheme to estimate variances due to sampled population (V P ), va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 26 publications
(40 reference statements)
1
55
0
Order By: Relevance
“…A number of studies have reported that comparisons of elemental compositions are useful for the forensic discrimination of glass fragments, 5,6,8,9,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and it is not pointed out again in this paper. What should be emphasized here is that a good correlation was observed in the elemental profiles between the non-heated and heated fragments in any of the 5 glasses.…”
Section: Comparison Of the Elemental Composition Between Heated And Nmentioning
confidence: 62%
See 1 more Smart Citation
“…A number of studies have reported that comparisons of elemental compositions are useful for the forensic discrimination of glass fragments, 5,6,8,9,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and it is not pointed out again in this paper. What should be emphasized here is that a good correlation was observed in the elemental profiles between the non-heated and heated fragments in any of the 5 glasses.…”
Section: Comparison Of the Elemental Composition Between Heated And Nmentioning
confidence: 62%
“…[1][2][3][4][5][6] The forensic glass comparison mentioned above has been conducted by measuring the refractive index (RI) [5][6][7][8][9][10][11][12][13][14] and conducting an analysis of the elemental compositions using procedures such as X-ray fluorescence spectrometry (XRF), 6,8,12,[15][16][17][18][19][20][21][22] inductively coupled plasma atomic emission spectrometry (ICP-AES) 8,15,[23][24][25] and mass spectrometry (ICP-MS). 5,6,9,12,18,[26][27][28][29] An RI measurement can be applied to a glass fragment smaller than 0.1 mm in a maximum width without its destruction. This method has another advantage of simple sample preparation and short measurement time.…”
Section: Introductionmentioning
confidence: 99%
“…Elemental analysis of glass is now commonly performed with inductively coupled plasma (ICP) optical emission spectrometry, ICPMS, X-ray fluorescence, or scanning electron microscopy; ICP provides better detection limits and discrimination power than other elemental techniques (25)(26)(27) ). An ICP mass spectrometer and a laser ablation (LA) sample introduction system used together offer the advantages of minimum removal of sample by LA and the excellent sensitivity and precision of ICPMS (28)(29)(30).…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Various techniques of elemental analysis have been proposed for discrimination of glass samples, such as XRF, [2][3][4][5] EPMA, 6 AAS, 7 NAA, 8 ICP-AES, 2,9,10 ICP-MS, [11][12][13] and LA-ICP-MS. 14,15 For discrimination of glass, ICP-MS can widely be used to perform multielemental analysis with higher sensitivity than other techniques. However, it is difficult to apply ICP-MS for analysis of a small glass fragment, since glass samples found at crime scenes are often extremely small.…”
Section: Introductionmentioning
confidence: 99%